Quantitative analysis of fat, oil and grease in valikamam area, Sri Lanka and conversion of waste oil into grease - Velauthamurty, kugamoorthy; Dilki Manisha, Kurukulasuriya (International Journal of Advanced Chemistry, 2016)
Groundwater is the main source of freshwater. Groundwater denotes to all the water occupying the voids, pores and fissures within geological formations, which originated from atmospheric precipitation either directly by rainfall infiltration or indirectly from rivers, lakes or canals. Groundwater pollution is a serious problem because many people depend on groundwater for their drinking water. Waste oil along with heavy metals is one of the major contaminant species makes water harmful. A one drop of heavy fuel oil is enough to contaminate a million gallons of freshwater. Waste oil is generated through dumping, land spreading, incineration, road oiling, industrial chemical spills, extensive use of pesticides, herbicides and fertilizers etc. For this study water samples were collected from forty of wells representing the Valikamam area. Then the water samples were analyzed for Fat, Oil and Grease using liquid-liquid extraction with hexane and gravimetric determination. The results shows only four wells exceed the 10 mg/L while thirty six wells were potable. Waste oil disposal is a big threat these days around the world. Hence this paper gives a brief review about recycling waste oil by converting it into commercially important lubricating grease. Once the grease characterization is done for the grease obtained from waste oil, we can bring it up to the commercial stage on the other hand giving a better solution for the depletion of waste oil.